Archiwa literatury kobiecej - Marzec, Lucyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
The article concerns the relationships between terms, frequent in Polish literary criticism, such as “women’s literature”, “women’s press”, “women’s writing”, “literature written by women” and ”Feminist literature”. The author discusses three research books that have been published recently in which slightly different categories have been applied and which, at the same time, focus on the female element of cultural texts. In addition, the author points at multiple tendencies, frequently dissimilar and distinct, in the approach to the relationship between gender and the text. At the same time the author emphasizes a certain disposition manifested by researchers to employ the gender category to judge literary works. Hence, it seems to be quite justified to reopen the Jy women to show them in a new light. The same applies to the surrounding discussions on relevant titles — just as it is the case with publications by Joanna Krajewska, Jerzy Strzelczyk and Kamilla Łozowska-Marcinkowska.